1994
DOI: 10.1002/mc.2940110406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcriptional activation of a cyclic AMP response element by 2,6,10,14‐tetramethylpentadecane (pristane) in JB6 mouse epidermal cells

Abstract: Pristane is a naturally occurring isoprenoid that is believed to be derived from the phytyl moiety of chlorophyll. Thus, it is not surprising that pristane is present in many common fruits and vegetables. Furthermore, pristane can be detected in the tissues of fish and mammals. In animal models using rodents, pristane can function as a potent tumor promoter. At the molecular level, pristane can induce changes in the plasma membrane, alter the conformation of chromatin, and selectively activate gene expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Pristane (2, 6, 10, 14‐tetramethylpentadecane), a naturally occurring isoprenoid is considered as a potent carcinogen [22]. Previous reports have shown that intraperitoneal injection of pristane induces plasmocytomas in BALB/c mice [23–25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pristane (2, 6, 10, 14‐tetramethylpentadecane), a naturally occurring isoprenoid is considered as a potent carcinogen [22]. Previous reports have shown that intraperitoneal injection of pristane induces plasmocytomas in BALB/c mice [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…Human breast adenocarcinoma (MCF‐7) cells injected to the pristane primed mammary fat pad of virgin female Wistar rat causes development of solid tumours, which have been characterized as adenocarcinoma or fibroadenoma [27]. Pristane‐induced tumours exhibit activation of several kinases such as protein kinase C (PKC) [25] and protein kinase A (PKA), enhanced activation of cAMP response element (CRE) [22] and c‐Myc and increased expression of various molecules such as cyclooxyge‐nase 2 (COX‐2), prostaglandin E receptor (EP)‐2, EP‐4 and inducible nitric oxide synthases (iNOS) [28, 29]. In this study, we sought to determine the role of OPN in pristane‐induced mammary tumourigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the disparity of the results obtained with TPA and pristane in protein kinase C substrate phosphorylation and activation of the chloramphenicol acetyltransferase genes [ 10 ] it appears that TPA and pristane exhibit different tumor promotion mechanism(s) of action in chemical carcinogenesis. TPA induces CYP1A and simultaneously suppresses CYP2B [ 15 ], but the mechanism of CYP1A induction by TPA appears to differ from other TPA inducible functions, as well as from those elicited by 3-MC [ 11 13 ]. TPA intercalates into DNA and modifies histone phosphorylation, thus altering the super-structure of chromatin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%